Analisis Hubungan Kepatuhan Farmakologis dan Kepatuhan Diet Rendah Natrium dengan Tekanan Darah Pasien Hipertensi di Beberapa Puskesmas Kabupaten Banyumas - Ristiana, Zahra Amalia; Fauziah , Fauziah; Setianingsih , Siti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Introduction: Hypertension is a chronic condition that requires long-term management through adherence to pharmacological therapy and a low-sodium diet. Both factors play an essential role in controlling blood pressure and preventing complications. Methods: This study employed a quantitative observational design with a cross-sectional approach conducted in February 2025 at four public health centers in Banyumas Regency. A total of 70 hypertensive patients enrolled in the PROLANIS program were selected using purposive sampling. Data were collected through interviews and health status documentation, then analyzed using the Chi-Square test and odds ratio (OR). Results: No significant relationship was found between pharmacological adherence and blood pressure (p systolic = 0.131; p diastolic = 0.434). Conversely, a significant association was observed between adherence to a low-sodium diet and blood pressure (p systolic = 0.000; p diastolic = 0.003). Odds ratio analysis indicated that patients adhering to a low-sodium diet were 1.86 times more likely to achieve controlled blood pressure compared to those who were non-adherent. Conclusion: Adherence to a low-sodium diet has a greater influence on blood pressure control than medication adherence. Therefore, educational interventions emphasizing the importance of dietary management and consistent medication intake should be optimized to improve the effectiveness of hypertension therapy in primary health care settings.